The Impact of Houses & Living Spaces During the Second World War in Gail Tsukiyama's The Samurai's Garden - Anugraha, Ressy; Clement, K. Shanthi (Journal of Neonatal Surgery, 2025)
The terms "shelter" and "home" are closely intertwined, each reflecting complex constructs that extend beyond human society to encompass all ecological beings on our planet. Michael Foucault, in his work Of Other Spaces, asserts that "the present epoch will perhaps be above all else the epoch of space" (Foucault 20). Thus, gaining a broader understanding of the relationship between individuals and their environments is crucial. The spatial dynamics of a house are particularly significant, as these spaces are where people's lives, psyche, and overall development unfold. The discourse surrounding the built environment represents a novel and under-explored area within literary studies. A more profound comprehension of how human actions interact with various environments can contribute to fostering sustainable practices, especially in the Anthropocene era. This paper examines the impact of the built environment, such as houses and living spaces, during the tumultuous period of the Second World War, focusing on Gail Tsukiyama's historical fiction, The Samurai's Garden. The researcher incorporates concepts from Environmental Psychology, which expands the definition of 'the environment' to include built spaces as integral components. This theoretical framework diversifies and enhances the discourse within literary environmental studies. This study aims to illuminate pro-environmental behaviors, advocate for sustainable environments, and explore the emotional resonance that the built environment holds for its inhabitants